A THOUSAND FIREFLIES IN MANHATTAN: TRANSLATION IN THE SHORT STORIES OF UMAR KAYAM - Harry Aveling (Soegijapranata Catholic University, 2005)
This paper discusses the techniques used by major Indonesian author Umar Kayam for presenting representations of American English and Javanese language and culture in his early Indonesian-language short stories, published as Sri Sumarah dan Cerita Pendek Lainnya in 1975. Using Vinay and Darbelnets list of translation strategies, the paper suggests that Kayam made extensive use of direct translation, especially literal translation with borrowings from English, and borrowings with Indonesian glosses for Javanese terms. He also uses calques and adaptations in a very few incidences.